Influence of genomic ancestry and self-reported color-race in CKD in a nationwide admixed sample of Brazilian patients with type 1 diabetes - Pizarro, Marcela Haas (Diabetes Metab Syndr Obes, 2019)
AIMS: Patients with diabetes that are African-Americans or Asians have a higher chance of developing diabetic nephropathy than Caucasian. Our objective was to evaluate the association between self-reported color-race, genomic ancestry, and the presence of chronic kidney disease (CKD), assessed by glomerular filtration rate and albuminuria in patients with type 1 diabetes. METHODS: This is a multicenter, observational, cross-sectional study with 1564 patients, conducted between August 2011 and August 2014 in 14 public clinics from 10 Brazilian cities. The ethnic aspects of the patients were evaluated using self-reported color-race and genomic ancestry (divided in European, African, and Amerindian). We divided the patients into groups: normal renal function and CKD. RESULTS: More patients self-declared themselves as black and brown in the group with CKD. The multivariate logistic analysis revealed that self-reported color-race was not associated with CKD and that a higher African ancestry was also not associated with CKD (p=0.06). Patients with an African ancestry of 50% or higher had an association with CKD that did not persist after the multivariate analysis. CONCLUSION: In our patients, from an admixed, multi-ethnic population, we did not find an association between self-reported color-race, genomic ancestry and CKD. It is important to note that despite the fact that we did not find a significant p-value in the multivariate analysis concerning African ancestry and CKD, we found a narrow confidence interval (0.961–3.98) with an OR of 1.956. Further studies should be conducted to confirm the lack of association between African ancestry and CKD, especially from populations with higher African or Amerindian ancestries to better understand the association between self-reported color-race and genomic ancestry with CKD.